Understanding the concept of diversity, abundance, and distribution of marine invertebrates through practicum students of the Biology Education, Pattimura University - Tuaputty, Hasan; Arini, Ine; Latupeirissa, Louvenska (BIOEDUPAT: Pattimura Journal of Biology and Learning, 2023)
The application of marine biology courses cannot be separated from field practicum activities which are integrated with the main scientific pattern of Pattimura University, namely build nobleh marine, meaning that the marine biology lecture process is a goal of developing human resources. One of the competencies of marine biology courses which emphasizes is that students must understand the life of various types of marine invertebrates that live in each coastal water ecosystem and must also master how to observe and research various types of marine invertebrate life found in each zone of coast (intertidal zone and subtidal). The results of the findings of various types of marine invertebrates were carried out by diversity analysis, the results were 2.0 <H'=2.363836 ≤ 3.0, meaning the level of diversity was medium. The relative density of invertebrates on various substrates includes sand 25%, density on sandy gravel substrates 9.9%, muddy substrates 11.4%, coral substrates 15%. The distribution patterns of various types of invertebrates can also be explained according to the results of analyzes including (1) clustered distribution patterns occur in Crustacea (Emita sp, Harpiosquilla raphidae, Ocypoda cursor), Gastropoda (Nerita polita, Conus sponalis), Bivalvia (Venerupis corrugate), (2) The distribution pattern is uniformly occurs in invertebrates of Bivalvia (Anadara broughtonii, Mytilus trossulus, Tridacna rosewateri, Pinctada radiate), (Diadema setosum, Holothuria scabra), Gasropoda (Strombus decorus). Proving the truth of the concept or theory of various types of invertebrates in biology courses the truth of the sea has been tested through field practicums in the coastal waters of Salahutu District, Ambon Island